Growth and yield performance of chili (Capsicum annum L.) influenced by greywater organo mineral liquid fertilizer - Tan, Si Li (2021)
Over the years, the increase in greywater disposal coincides with the rapidly growing world population. Current literature shows a high valuable fertilizing potential of laundry greywater owing to its salts and nutrients contents. Thus, the objectives of this research were to formulate a potential liquid organo mineral fertilizer (OMF) from laundry greywater (LW) and vegetable wastes (VW) and to investigate the effects of organo mineral fertilizer on the growth and yield performance of chili plants in fertigation system. In the first experiment, vegetable waste was dissolved in laundry greywater at 3 ratios (1:10, 1:15, and 1:20) and shaken to obtain a biological suspension. Then, samples were subjected to an incubation period of 0, 3, 6, 9, 12 and 15 days respectively. Data on pH, electrical conductivity (EC), the concentration of nutrients (N, P, K, Ca, Mg, Mn, Cu, Zn, and Fe) of each sample were recorded at the end of the experiment. In second experiment, selected OMF from previous experiment was tested on chili plants in five treatments including 100 % AB fertilizer (ABF), 75 % ABF + 25 % OMF, 50 % ABF + 50 % OMF, 25 % ABF + 75 % OMF and 100 % OMF on 10 chili plants each in separate fertigation systems under the rain shelter. Growth measurements along with yield performance as well as the proximate compositions of fruits and microorganism count were analysed. Both experiments were laid out in a Completely Randomized Design (CRD). Data collected was analysed using SAS and the treatment means were compared by using Tukey test at a 5 % significant level. At a lower ratio (1:10) of VW:LW with an incubation period of 9 to 15 days, the best quality of liquid OMF was produced. Moreover, the combined use of ABF and OMF resulted in better growth of chili plants and their fruits. The sole application of OMF produced statistically similar chili fruits as commercial ABF in terms of fruit quality. Thus, it is recommended to enhance the growth and yield performance of chili by mixing ABF and OMF at a ratio of 50:50. As the product is produced from waste, OMF may considerably reduce fertilization costs and improve the sustainability of the farming system. Meanwhile, further studies on the enhancement of phosphorus content in the fertilizer and microorganism activities related to the application of fertilizer are needed to improve the overall performance of fertilizer.